Mamíferos de la Reserva del Valle de los Cirios, Baja California, México - Ríos, Evelyn; Álvarez-Castañeda, Sergio Ticul (Instituto de Ecología, A.C., 2002)
The Valle de los Cirios is the largest natural reserve in Mexico, but has received little attention. Indeed, the Peninsula of Baja California is the region with the largest number of endemic subspecies of mammals in the country, however, survey to studies the diversity of terrestrial mammals in the region are few. Moreover, the Reserve has no inventory of its mammals. In 1998, we surveyed the Reserve to create an inventory of mammals species and subspecies, and their distribution. Specimens were collected at 40locations, including the different plant communities in the reserve. We document the presence of five orders, 11 families, 21 genera, 27 species, and 38 subspecies. This represent about 6% of mammals species reported for Mexico. The distribution of Perognathus longimembris and Reithrodontomys megalotis is extended. The reference collection was formed with 919 specimens. A species is listed in the Norma Ofical Mexicana (2000); there are seven endemic subspecies within the Valle de los Cirios. Since the area is inexcellent conditions of conservation, it is a suitable place for different mammalian studies.